PENGARUH KUALITAS PELAYANAN DAN FASILITAS KANTOR TERHADAP KEPUASAN MASYARAKAT DI KECAMATAN PUNGGUR KABUPATEN LAMPUNG TENGAH - M Sobri Kurniawan; Marzuki Noor; Suharto Suharto (SIMPLEX: Journal of Economic Management, 2021)
This study aims to determine and test empirically: The Effect of Service Quality on Community Satisfaction at the Punggur District Office, Central Lampung Regency. The Effect of Office Facilities on Community Satisfaction in the Office of Punggur District, Central Lampung Regency. The Effect of Service Quality and Office Facilities on Community Satisfaction at the Punggur District Office, Central Lampung Regency. Respondents in this study were 58 people who administered family cards, ID cards and other documents at the Punggur District Office, Central Lampung Regency. The results of the study prove that there is an effect of service quality on community satisfaction at the Punggur subdistrict office, Central Lampung regency, there is an effect of office facilities on community satisfaction at the Punggur subdistrict office, Central Lampung district, there is an effect of service quality and office facilities on community satisfaction at the Punggur district office, Lampung regency Middle. The magnitude of the influence of service quality and office facilities on community satisfaction at the Punggur subdistrict office, Central Lampung district is 49.4%, while the remaining 50.6% is influenced by other factors outside the model included in this study